Understanding John Guare - Demastes, William W. (Book collections on Project MUSE., 2017)
"John Guare, one of the most innovative and influential contemporary American playwrights of the last sixty years, is best known for such works as House of Blue Leaves, winner of an Obie Award, the New York Drama Critics Circle Award for Best American Play, and four Tony Awards, and Six Degrees of Separation, recipient of the New York Drama Critics Circle Award for Best American Play and the Olivier Best Play Award and a finalist for the Pulitzer Prize in Drama. In Understanding John Guare, William W. Demastes provides a concise biography and analyzes the playwright's career from his earliest works produced off-off Broadway in the 1960s to his most recent Broadway play, A Free Man of Color, a finalist for the 2011 Pulitzer Prize in Drama. Often compared to his contemporaries Sam Shepard and David Mamet, who have distinctive voices tied to their mastery of realistic, idiomatic American English, Guare has a style that is perhaps more varied, Demastes speculates, the result of his formal training in theater. After earning a bachelor's degree from Georgetown University, Guare earned an M.F.A. from the Yale School of Drama. He then polished his theater craft in New York City during the exciting and turbulent 1960s, breaking from realist conventions and creating an unlikely blend of comedy, burlesque, stand-up comedy, and absurdly incongruous plotlines. The result has been a theater of surprise, rich in stage action, and experimentally invigorating. Demastes examines Guare's tools and techniques such as mixing serious with comic, creating characters who break into song and dance, inserting standup comedy routines, and drawing from the most absurd incongruities of everyday life. In doing so, Guare has created plays about the best and worst of humanity, about lost souls, and about delusional ideals."--